Rethinking The Performance Appraisal: Between Evaluational and Motivational Puposes - Bagus Riyono (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 1998)
There are two main purposes of performance appraisal. First, it is done to evaluate the past performance of employees in order to give sufficient and necessary data for personnel decision making. This calledevaluational purpose. Second, it is be is meant to one of the strategies to motivate employees in order to increase their productivity. This one is called motivational purpose (Roberts & Pavlak, 1996). Most of researches on performance appraisal focused on the appraisal processes that govÂerned by the evaluational paradigm, while motivational purpose. which is also the ultimate purpose of performance appraisal (Roberts & Pavlak,1996), is not widely researched yet (see appendix). This paper discusses the differences between those two paradigms and argue why the focus should be shifted from eva/uffonal to motivational porpuse. The proposed characteristics of a new performance appraisal design is also discussed. Key Words : Evaluational Paradigm, Motivational Paradigm, PerformanÂ ce Targeting, &bjedive Judgement, Corrparison Standard.